Characteristics of Laryngopharyngeal Reflux: A retrospective descriptive study - Rizka Fathoni Perdana; Reyna Cesariyani Rahmadianti Rusuldi; Husin Thamrin; Rosa Falerina (Universitas Muhammadiyah Surabaya, 2022)
Laryngopharyngeal reflux (LPR) is a condition of reverse flow of gastric and duodenal fluid that reaches the aerodigestive tract, causing inflammation in the upper respiratory tract. Reflux Symptoms Index (RSI) and Reflux Finding Score (RFS) have been used as instruments to determine the symptoms and signs in LPR patients. This study aims to find out the characteristics of patients with LPR. A retrospective descriptive study was performed using medical records as a source of information to obtain the characteristics of patients with LPR in ENT Outpatient Clinic Dr. Soetomo General Academic Hospital Surabaya. The study population is all patients that has been diagnosed with LPR based on RSI >13 and RFS >7 in the period 2018-2019. Our finding shows the total patients diagnosed with LPR were 58. There were 45 patients diagnosed solitarily according to the results of the RSI score, while the RFS was 34 patients. The total patients diagnosed according to both of RSI and RFS were 21 patients. In this study, 67.24% patients with LPR were female, while the male patients were 32.76%. Most patients with LPR belonged to 50 – 59 years (25.86%). The distribution of occupation shows the highest number of patients is unemployed (43.10%). The most frequent and severe complaints from LPR patients were throat clearing, sensation of something sticking in throat or lump, and excess throat mucus or postnasal drip. The laryngoscopy findings compiled on the RFS showed that the most common signs in LPR patients were subglottic edema, thick endolaryngeal mucus, and posterior commissure hypertrophy.